Gross Morphological Studies of Rumen of Sheep (Ovis aries) Fetus - Rajyalakshmi, Thota; Chandana, G S S; Bhagyalakshmi, J; Chowdary, Sudharani (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present study was conducted on healthy normal embryos and fetuses of either sex of sheep which were collected immediately after slaughter of animals from abattoirs. The embryos/ fetuses were divided as group I (1-75 days of gestation) and group II (76 days to end of gestation) with six specimens from each group. The gross morphological studies showed that at 47 days of gestation, all the four stomach compartments were distinguished and the rumen was a tiny sac-like structure with thin walls and was situated in the left side of the abdominal cavity. Caudal transverse groove, right and left longitudinal grooves were clearly distinct and these grooves separated rumen into dorsal, ventral, caudo-dorsal, and caudo-ventral sacs. The rumen’s internal surface was glossy and smooth, devoid of papillae and divided into dorsal, ventral, caudo-dorsal, and caudo-ventral sacs by the formation of left longitudinal, right longitudinal, and caudal transverse cranial transverse pillars. The rumeno-reticular fold was observed at the end of gestation, i.e., 140 days of gestation with tinny papillae and the papillae more developed behind the rumeno-reticular fold.